PERSEPSI MANFAAT DAN RISIKO DALAM PERILAKU PEMBELIAN KONSUMEN ONLINE SHOP - Yuliati, Lilik Noor; Simanjuntak, Sylvia (Jurnal Ilmu Keluarga dan Konsumen, 2011)
This study was to analyze lifestyle, perceived risks, perceived benefits, online searching, evaluation of information, and consumer purchasing behavior in online shop. Online shop election conducted purposively, that was facebook, kaskus, and online shop community. The study included 145 consumers. Data analysis was performed by descriptive, different test, and regression test. The results showed that perceived risks, evaluation of information, and online shopping expenditure among groups that worked and didn’t work differ significantly. Consumers had lifestyle in moderate category, perceived risk in risk category, neutral perceived benefits, and low online searching. Perceived benefits was influenced by gender, age, occupation, income, and lifestyle, while the perceived risks was influenced by work and lifestyle. Online search influenced by gender, while evaluation of information was influenced by gender, perceived benefits, and perceived risks. Fashion product buying behavior was influenced by gender, age, occupation, lifestyle, perceived benefits, online searching, and evaluation of information.